2015
DOI: 10.1016/j.jval.2015.09.1412
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Societal Cost Benefits Of Increasing Patient Satisfaction By Using An Inhaler With Improved Features Compared To Spiriva® Handihaler® For The Management Of Chronic Obstructive Pulmonary Disease (Copd) In The Uk

Abstract: was based on the average monthly salary in the UK. A conservative assumption was made about the increased risk of a productive day being lost -associated with level of patient satisfaction to their treatment -by calculating an approximate number of unscheduled hospitalisations that users of a new inhaler would experience in the previous 12 months relative to Spiriva® HandiHaler®. Patient satisfaction with their inhaler was based on inhaler features that relate to ease of use and ergonomics and compared Spiriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent multinational real-world study of COPD patients identified a direct link between improved inhaler satisfaction (mainly durability, ergonomics, and ease-of-use) and increased treatment adherence 51. Hence, improved patient satisfaction with an inhaler may improve clinical and economic outcomes in patients with COPD 31,51. Notably, a recent study on the potential societal costs and benefits of improving treatment satisfaction, by use of a new tiotropium inhaler that was comparable to HandiHaler, estimated that 59% of patients preferred the new inhaler 31.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent multinational real-world study of COPD patients identified a direct link between improved inhaler satisfaction (mainly durability, ergonomics, and ease-of-use) and increased treatment adherence 51. Hence, improved patient satisfaction with an inhaler may improve clinical and economic outcomes in patients with COPD 31,51. Notably, a recent study on the potential societal costs and benefits of improving treatment satisfaction, by use of a new tiotropium inhaler that was comparable to HandiHaler, estimated that 59% of patients preferred the new inhaler 31.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, improved patient satisfaction with an inhaler may improve clinical and economic outcomes in patients with COPD 31,51. Notably, a recent study on the potential societal costs and benefits of improving treatment satisfaction, by use of a new tiotropium inhaler that was comparable to HandiHaler, estimated that 59% of patients preferred the new inhaler 31. Moreover, patients who switched to the new inhaler reported a ~32% improvement in satisfaction with treatment and a 9% increase in adherence 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation